Effectiveness of propolis in dental applications: A review study (Research, Society and Development, 2024)
Propolis, a natural resinous substance produced by bees, has received attention in dentistry for its potential therapeutic properties. The objective of this study is to review the existing literature on the efficacy of Propolis in various dental applications, highlighting its antimicrobial, anti- inflammatory, antifungal and healing properties. The search included the PubMed, Scopus, Web of Science, and Google Scholar databases using key terms such as "propolis," "dentistry," "oral health," "antimicrobial," and "anti-inflammatory." The studies included in this review were clinical trials, literature reviews, systematic reviews, and meta-analyses published in English, Spanish, or Portuguese. The results highlight the efficacy of propolis in diverse dental contexts, especially its antimicrobial action against oral pathogens such as Streptococcus mutans and Candida species. In addition, propolis has demonstrated beneficial anti-inflammatory effects for the treatment of oral mucosal conditions and gum inflammation. The diverse chemical composition of propolis, including flavonoids, phenolic acids, and terpenes, contributes to its therapeutic potential in dentistry. It is concluded that propolis has promising therapeutic applications in dentistry, showing itself as a natural or complementary alternative to conventional dental treatments. More research is needed to standardize their formulations and dosages for optimal clinical use in oral health.